A novel green biosorbent from chitosan modified by sodium phytate for copper (II) ion removal. (9th August 2017) - Kong, Aiqun; He, Benqiao; Liu, Guangrui; Lu, Xiaosong; Hao, Yingdong; Bao, Xinyao; Yan, Feng; Li, Jianxin
Abstract : A novel kind of adsorbent bead was prepared from chitosan (CS) by ionic‐linked with sodium phytate (SP) and then covalent cross‐linked with epichlorohydrin (ECH) by nonsolvent‐induced phase separation. The structure of the beads was characterized by scanning electron microscopy, Fourier transform infrared spectroscopy, and X‐ray photoelectron spectroscopy. The adsorption properties of the beads for Cu(II) ions under different adsorption conditions were investigated. The maximum adsorption capacity of Cu(II) ions was 177.1 mg g −1 at the conditions of pH of 5.2, temperature of 50°C, and initial Cu(II) ion concentration of 728.3 mg L −1 . The adsorption isotherm of Cu(II) ions on the CS/SP/ECH beads was well correlated with the Langmuir isotherm model, and the whole adsorption process could be better followed the pseudo‐second‐order kinetic model. Moreover, the CS/SP/ECH beads still exhibited good adsorption capacity even after the 15th regeneration cycles.